Актуальные вопросы оптимизации учебного процесса у будущих стоматологов - Зидрашко, Г. А.; Алиева, Е. Г.; Сулаева, О. Н.; Таврог, М. Л.; Варакута, О. А.; Зідрашко, Галина Анатоліївна; Алієва, Олена Геннадіївна; Сулаєва, Оксана Миколаївна; Таврог, Маріанна Львівна; Варакута, Ольга Анатоліївна; Zidrashko, G. A.; Alieva, E. G.; et al. (My University, 2016)
Показан опыт использования современных технологий, которые в комплексе значительно повысили эффективность обучения будущих стоматологов при усвоении дисциплины «Гистология, цитология и эмбриология», что подтверждено на протяжении 5-ти лет результатами лицензионных экзаменов «Крок 1 «Стоматология». Відбито досвід використання сучасних технологій, які значно підвищили ефективність навчання майбутніх стоматологів при засвоєнні дисципліни «Гістологія, цитологія та ембріологія», що підтвердили протягом 5-ти років результати ліцензійних іспитів «Крок 1 «Стоматологія». Introduction. The actual question of the modern stomatology is the question related to the increase of efficiency of educational process of future doctors-stomatologists. Research purpose. To inculcate in the department of Histology, cytology and embryology of the Zaporizhzhya state medical university new teaching technologies and to study quality of education at their use during 5 years. Object and methods of the research. A research object is students of the first course of medical faculty of the Zaporizhzhya state medical university trained on the speciality ‘Stomatology’, in which educational process the complex of two types of the control test systems was inculcated, ‘Practicum of histology, cytology and embryology’ for the students of speciality ‘Stomatology’, methodical working-out and new computer technologies. Results of researches and discussion. For the increase of knowledge level of histology, cytology and embryology of future stomatologists credit-module educational system has been implemented in the department of Histology, cytology and embryology of the Zaporizhzhya state medical university in conjunction with the complex use of two kinds of test systems for routine and module control. Forms and methods of independent work of students during class hours have been improved. For preparation for practical classes students widely use methodical recommendations, collections of tests and the original album “Practicum of histology, cytology and embryology” for the students of speciality “Stomatology”, developed by the teachers of the Department of Histology, Cytology and Embryology Zaporizhzhya State Medical University. The algorithm of independent work of students for the study of histological microslides, the main theoretical material, classifications, schemes of the morphological structure of organs and systems for the studied topic are presented in the “Practicum”. Modern computer technologies always are used in lectures and practical classes. Conclusions The use of modern teaching technologies in the Department of Histology, Cytology and Embryology of the Zaporizhzhya state medical university such as: implementation of the credit-module educational system, complex use of two types of the test systems for realization of current and module control, introduction in the educational process of “Practicum on histology, cytology and embryology for the students of speciality “Stomatology”, and training manuals, collections of tests and situational tasks, and also using of new computer technologies greatly enhanced the effectiveness of the training of future doctors-stomatologists. This is objectively confirmed by the results of an licensed examination “Step 1” “Stomatology” during 5 years. These educational technologies allow each student to study the theoretical material and develop practical skills in classes.
Актуальні питання оптимізації навчального процесу у майбутніх стоматологів
Actual questions of the optimization of educational process for future stomatologists
Keywords: оптимизация; современные технологии в обучении; самостоятельная работа; кредитно модульная система; оптимізація; сучасні технології в навчанні; самостійна робота; кредитно модульна система; optimization; modern technologies in education; independent work; credit module system